Innovation for Sugarcane Planting Material in Ryland Farming - Devita Areifvia Ningsih; Taryono Taryono; Rani Agustina Wulandari (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2018)
Sugar productivity of sugarcane is dependent on stalk yield and sucrose content which both influenced by planting material. Due to the important of planting material, this study is intended to examine the influence of planting materials i.e. cutting as a control, bud set and bud chip, toward seed quality and the early growth of cane plant in the field. This study was arranged in completly randomized design, with two factors, which are six clones of sugarcane and three types of seedling materials. The results showed that there was an interactions between both factors on germination rate, vigor index, leaf numbers, internode numbers, tiller numbers, leaf area, root volume, root fresh weight, root dry weight, shoot fresh weight, and shoot dry weight. The early growth of seedling was dependent on the clone. According to shoot fresh weight, cutting was suitable for PS 881 and Bululawang. Bud set for PS 864 clone, whereas bud chip for PSJT 941 and Kidang Kencana. Three seedling materials could be fitted to Bululawang and VMC 86-550, however for dryland farming bud sett and bud chip are preferred because such planting materials can be germinated first at the nursery and then transplantted in the field when there has been enough water content in the soil.